The Role of Tumor-Infiltrating Lymphocytes in Ovarian Cancer Prognosis: A Systematic Review on Immune Subtypes and Spatial Distribution - Kusumastuti, Sanindita; Hellyanti, Tantri; Kodariah, Ria (Indonesian Journal of Cancer, 2026)
Background: Tumor-infiltrating lymphocytes (TILs) are key components of the immune microenvironment in ovarian cancer, influencing disease progression and clinical outcomes. However, the prognostic significance of different TIL subtypes, including CD8+, CD4+, FOXP3+ regulatory T cells, and CD20+ B cells, remains inconsistent across studies. This systematic review aims to synthesize current evidence on the prognostic roles of these immune subtypes, with a focus on their spatial distribution within the tumor microenvironment and associations with overall survival (OS) and progression-free survival (PFS) in ovarian cancer. Methods: A systematic search was conducted using the PRISMA 2020 guideline protocol and was registered under PROSPERO with registration number CRD42025638744. Several databases, including PubMed, Scopus, and Google Scholar, were included to obtain articles, using keywords related to ovarian cancer, TILs, immune subtypes, and prognosis. Studies published in peer-reviewed journals without time restrictions were included. Selection criteria focused on studies that reported the density and localization of TIL subtypes and their association with clinical outcomes.Results: Fifteen studies met the inclusion criteria, involving 7,982 ovarian cancer patients. CD8+ TILs, together with CD20+ B cells and memory T cells, were consistently associated with better clinical outcomes, particularly when localized within intraepithelial regions. CD4+ T cells exhibited diverse prognostic effects depending on their polarization, where FOXP3+ regulatory T cells were linked to poor prognosis due to their immunosuppressive functions. The spatial distribution of TILs was a critical determinant of their prognostic value, with intraepithelial TILs showing stronger anti-tumor activity than stromal TILs. Variability in detection methods, cut-off values, and tissue sampling contributed to inconsistencies across studies.Conclusion: While TILs phenotypes may predict clinical outcome in ovarian cancer patient, their spatial distribution must be taken into consideration to sharpen analysis. To establish a more reliable prognostic marker, methodologies using standardized TIL thresholds should be implemented, hence the need for further studies.